Arabic Literary Influences and Representations in the Poetry of Iqbal: A Cultural and Thematic Analysis - Ahamed Zubair K M A Dr; Nahvi Muhiyadeen Lebbai; M.Yasar Arafath Ali; N Sheik Hameed M; Luthfur Rahman (Ijaz Arabi Journal of Arabic Learning, 2026)
This research examines the representations and influence of Arabic literature in the poetry of Muhammad Iqbal, renowned as the poet of the East. Despite never traveling to Arab lands, Iqbal's profound mastery of the Arabic language and literature profoundly shaped his poetic style, themes, and symbolism. The study employs a literary-analytical approach to identify how Iqbal drew from classical Arabic poetry, Quranic texts, and Arab cultural history. Through close reading of poems such as "The Mosque of Córdoba" and "Khidr-e-Rah," the analysis reveals his extensive use of Arabic vocabulary, adaptation of motifs like ruins and longing (al-atlal), and symbolic references to Arab figures and history. The findings demonstrate that Iqbal creatively reshaped these elements to formulate a modern poetic discourse centered on Islamic revival and civilizational renewal. His work thus serves as a bridge between classical Arabic literary traditions and contemporary Islamic thought. This study highlights the centrality of Arabic heritage in Iqbal's vision and contributes to understanding the intertextual connections within the Islamic literary sphere.